Model Pengembangan Pariwisata Kreatif Melalui Wisata Edukasi Dan Kuliner Di Sentra Jajanan Pasar, Pudak Payung, Kota Semarang - Nina Mistriani; Hesky Ilham Ikhlasandi; Vida Vrisna Kirani; Nakmas Syaefullah Fajrin; Elsandar Ndruru; Wisnu Teguh Prabowo; Widayanti Laia; Dyah Palupiningtyas (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
The development of the creative economy tourism sector is an initiative to improve the community's economy and accelerate tourism, including the city of Semarang. Pudak Payung Market, a traditional snack center has great potential as a creative tourist destination. This research aims to examine the development of creative tourism involving the community in Semarang City's traditional snack centers as a promotion for Semarang City in increasing tourist visits. This type of research is descriptive qualitative and uses a case study research method. This research has a community-based participatory approach that includes local activities in tourism development and promotion. Research result creative tourism development model to combine local wealth with educational and gastronomic tourism to increase tourist visits, strengthen local communities, and protect culture and the environment. So, the Pudak Payung Market Snack Center in Semarang City can be a successful example of creative tourism development in other areas.